Peningkatan Motivasi Belajar Dalam Mata Pelajaran IPA Melalui Metode MAke A Match Pada Siswa Kelas VI Semester 1 SD Myhammadiyah Blora Tahun 2015/2016 - FITRI WIJAYA, BUBUH, Drs. Suwarno, SH., M. Pd (2015)
The decline in motivation to learn science students due to lack of class VI student's ability to learn, students who lack the courage for expression skills, learning monotonous, lack of teachers in the use of varied teaching strategies and methods. This study aims to increase the motivation to learn science through learning methods Make A Match in Class VI Semester SD Muhammadiyah Blora. This type of research in the form of classroom action research with research subjects are six graders Muhammadiyah Blora totaling 34 Data collection methods used by obserrvasi, field notes, tests and documentation of students. The data analysis technique used is descriptive comparative data collection, data presentation/and conclusion. The results showed that an increase motivation to learn science that can be seen from the improvements of indicators that include 1) the passion and desire to succeed in a study before action of 25%, 62.5% the first cycle, the second cycle of 87.5% 2) The desire and need to learn the spirit of prior acts of 30%, the first cycle of 75%, 93.5% second cycle, 3) Having hopes and dreams ahead before action 20%, the first cycle of 75%, the cycle II 87.5%, 4) The existence of the award in the learning process before action 62.5%, 68.75% the first cycle, the second cycle 93, 75%, 5) The existence of a conducive environment for learning well before action of 50%, 68.75% the first cycle, the second cycle of 87.5% and the data on the achievement of learning outcomes of students score ≥ 71 before action 41.6%, 79.1% the first cycle and the second cycle 95.8%.The conclusion of this study is that through learning method Make A Match can increase learning motivation that the final impact on the outcome of sixth grade students learn science SD Muhammadiyah Blora the first half year 2015/2016.